Neutrophils Alter the Inflammatory Milieu by Signal-Dependent Translation of Constitutive Messenger RNAs - Lindemann, Stephan W.; Yost, Christian C.; Denis, Melvin M.; McIntyre, Thomas M.; Weyrich, Andrew S.; Zimmerman, Guy A.; White, Raymond L. (Proceedings of the National Academy of Sciences - PNAS, 2004)
The mechanisms by which neutrophils, key effector cells of the innate immune system, express new gene products in inflammation are largely uncharacterized. We found that they rapidly translate constitutive mRNAs when activated, a previously unrecognized response. One of the proteins synthesized without a requirement for transcription is the soluble IL-6 receptor α, which translocates to endothelial cells and induces a temporal switch to mononuclear leukocyte recruitment. Its synthesis is regulated by a specialized translational control pathway that is inhibited by rapamycin, a bacterial macrolide with therapeutic efficacy in transplantation, inflammatory syndromes, and neoplasia. Signal-dependent translation in activated neutrophils may be a critical mechanism for alteration of the inflammatory milieu and a therapeutic target.